Sustainability of rainwater harvesting systems in rural catchment of Sub-Saharan Africa - Pachpute, J.S.; Tumbo, S.D.; Sally, Hilmy; Mul, Marloes L. (Springer, 2009)
Sustainability of rainwater harvesting in enhancing water productivity in various biophysical and socioeconomic conditions of SSA is a key in large scale livelihood improvement. A study was undertaken in Makanya catchment of rural Tanzania to assess sustainability of storage type of rainwater harvesting systems including microdam, dug out pond, sub-surface runoff harvesting tank and rooftop rainwater harvesting system. The increasing population in upstream areas of the catchment has forced use of RWH systems for streams and river water abstraction. The agricultural intensification in hillslopes has affected the water availability for downstream uses. Rainfall variability, runoff quality and quantity, local skills and investment capacity, labour availability and institutional support influence sustainability of rainwater harvesting systems.